Dataset to manuscript "Trans-cis isomerization kinetics of cyanine dyes reports on the folding states of exogeneous RNA G-quadruplexes in live cells" accepted for publication in Nucleic Acids Research - Akira Kitamura; Johan Tornmalm; Baris Demirbay; Joachim Piguet; Masataka Kinjo; Jerker Widengren (Royal Institute of Technology, 2021)
This folder contains all raw data underlying the results presented in a manuscript, accepted for publication in Nucleic Acids Research, and entitled:

Trans-cis isomerization kinetics of cyanine dyes reports on the folding states of exogeneous RNA G-quadruplexes in live cells

Authored by:

Akira Kitamura2,*, Johan Tornmalm1,*, Baris Demirbay1,  Joachim Piguet1, Masataka Kinjo2, Jerker Widengren1+

1 Experimental Biomolecular Physics, Department of Applied Physics, Royal Institute of Technology (KTH), Stockholm, Sweden

2 Laboratory of Molecular Cell Dynamics, Faculty of Advanced Life Science, Hokkaido University, Sapporo, Japan

*  Contributed equally

+ To whom correspondence should be addressed. Email: jwideng@kth.se. Tel: +46-8-7907813

The data files are grouped into the different techniques used to generate them, and refer to the figures/tables in the manuscript where the extracted results are presented.

ABSTRACT

Guanine (G)-rich nucleic acids are prone to assemble into four-stranded structures, so-called G-quadruplexes. Abnormal GGGGCC repeat elongations, and in particular their folding states, are associated with amyotrophic lateral sclerosis and frontotemporal dementia. Due to methodological constraints however, most studies of G quadruplex structures are restricted to in vitro conditions. Evidence of how GGGGCC repeats form into G-quadruplexes in vivo is sparse. We devised a readout strategy, exploiting the sensitivity of trans-cis isomerization of cyanine dyes to local viscosity and sterical constraints. Thereby, folding states of cyanine-labeled RNA, and in particular G-quadruplexes, can be identified in a sensitive manner. The isomerization kinetics, monitored via fluorescence blinking generated upon transitions between a fluorescent trans isomer and a non-fluorescent cis isomer, was first characterized for RNA with GGGGCC repeats in aqueous solution using fluorescence correlation spectroscopy and transient state (TRAST) monitoring. With TRAST, monitoring the isomerization kinetics from how the average fluorescence intensity varies with laser excitation modulation characteristics, we could then detect folding states of fluorescently tagged RNA introduced into live cells.
Keywords: Physical Sciences; Fysik